Investigation on premixed H2/C3H8/air combustion in porous medium combustor for the micro thermophotovoltaic application. (15th February 2020) - Peng, Qingguo; Yang, Wenming; E, Jiaqiang; Xu, Hongpeng; Li, Zhenwei; Tay, Kunlin; Zeng, Guang; Yu, Wenbin
Highlights: Premixed H2 /C3 H8 /air combustion with and without porous medium are investigated. Ten kinds of porous medium are studied to boost the combustor thermal performance. Effects of propane blended ratio and porous medium parameters are analyzed. The electrical power and efficiency of the thermophotovoltaic system are compared. Abstract: The study of premixed H2 /C3 H8 /air combustion in the combustor inserted with porous medium (PM), which involved ten kinds of PM and varied with porosity, wire diameter and pores per inch (PPI), is experimentally and numerically conducted. Moreover, in order to boost the electrical power output and efficiency of the micro thermophotovoltaic (TPV) system, the effects of flow rate and propane blended ratio of the fuel on combustion and the thermal performance are investigated. The results indicate that the flame stability and heat transfer of premixed H2 /C3 H8 /air combustion can be significantly enhanced in PM. The 10% propane blended fuel effectively changes the flame location and temperature, as well as the thermal performance of the combustor and the outer wall temperature distribution, while the thermal properties of the combustor are less decreased with 15% propane added. It is also found that the combustor inserted with PM, which has an areal density of 0.0524–0.0551 g/cm 2 (PM #30-0.2, #60-0.14 and #80-0.12) and a porosity of 0.9, achieves the highest mean wall temperature and provides a high and uniform wall temperature at different inlet flow rates. The combustor inserted with PM #30-0.2 achieves the electrical power output 2.02 W and efficiency 1.6% for the micro TPV system under the condition of fuel flow rate 400 mL/min, propane blended ratio 12% and equivalence ratio 0.8.